PENGEMBANGAN PRODUKSI BIOPLASTIK UNTUK KERAJIANAN ASESORIS DARI GLISEROL SEBAGAI PEMANFAATAN LIMBAH INDUSTRI BIODISEL - Ratnani, Rita Dwi; Budihardjo, Arief; Wikanta, Deddy Kurniawan (Laporan Penelitian dan Pengabdian Masyarakat, 2024)
Plastics is one of chemical invention that make our life easier. The broaden usage of plastics is caused by plastic‘s preeminence. However, the preeminence of platics has made it as the biggest source of pollutant. Plastics create so much pollution and landfill crisis that various attempts have been made to solve these problems. One of these attempts is to create a biodegradable plastic from glycerol in Sequencing Batch Bioreactor. This research objectives are to develop the sequenching batch bioreactor for PHA production from glycerol and to optimize the process condition toward the PHA productivity. Research on the production of polyhydroxyalkanoates through the glycerol fermentation in a sequencing batch bioreactor is investigated both experimentally and modelling. The research sequences are conducted in several steps: design and fabrication of sequencing batch bioreactor, polyhydroxyalkanoates productivity test and optimization of the process parameters. The productivity test showed that the addition of methanol in the pretreatment process of PHA recovery has enhance the yield of the PHA extracted from the biomass. The highest PHA recovery was achieved from pretreament duration of 2 hours submerging in methanol solution. The optimization process showed that the most influencing variables was the nitrogen concentration and the highest PHA recovery was achieved from process conducted with nitrogen concentration of 4 mg/L, Phosporous concentration of 2 mg/L, oxygen concentration of 5 mg/L and the aerobic-anaerobic ratio of 1:4